ANATOMY OF RENAL DENERVATION DURABILITY. (April 2021) - Sharp, Andrew; Tunev, Stefan; Schlaich, Markus; Lee, David; Finn, Aloke; Melder, Robert; Trudel, Julie; Kandzari, David
Abstract : Objective: Safety and efficacy of catheter-based renal denervation (RDN) have been demonstrated in previous randomized, sham-controlled trials. Ongoing registries also suggest long-term durability of the RDN procedure. However, the exact mechanisms for RDN durability have not been previously elucidated. This report aimed to characterize the pathophysiological processes post radiofrequency (RF) RDN that translate into procedural durability utilizing animal models. Design and method: Animal studies were conducted in accordance with published guidelines. RDN was performed using the Symplicity RDN system (Medtronic, Santa Rosa, CA, USA) and the multielectrode RF Symplicity Spyral catheter in 164 healthy swine. Serial histological tissue samples were obtained 7, 28, 60, and 180 days post-procedure and followed by immunohistochemical and histopathologic analysis of RF-treated regions, sympathetic nerves and renal cortical axons. Results: At 7 days post-RDN, inflammation and swelling predominated the nerve lesions at the treatment site. A progressive nerve deterioration accompanied by Schwann cell reaction occurred over time leading to terminal atrophy and fibrosis at 180 days post-RDN. Nerve atrophy also became present distal to the treatment site. Although new Schwann cells appeared post-RDN, they failed to form the characteristic nerve fascicles and bundles which would reconstitute normal nerve morphology and support functional axons. Quantitative comparison of nerve necrosis and nerve atrophy indicated that proximal nerve necrosis peaks in the treated segments of the vessel, whereas nerve atrophy and low-grade nerve inflammation originates at the region of peak necrosis and extends distally beyond the RDN lesion. Thus, despite anatomic Schwann cell regeneration, the functional axonal nerve component did not recover. Conclusions: Histological analyses of porcine tissues demonstrated that terminal atrophy and fibrosis of the renal nerves developed within 180 days post-RF RDN procedure. Although new Schwan cell formation occurred, it did not reconstitute native nerve morphology suggesting functional nerve recovery is unlikely.